Remittances-finance-growth trilogy: Do remittance and financial development complement or substitute each other to affect growth in Nigeria? - Dada James Temitope; Akinlo Taiwo (Ekonomski Anali, 2023)
The study examines the absorptive role of financial development in the remittance-growth nexus in Nigeria between 1986-2017. In particular, the shortrun, long-run, and causal links between remittances, financial development, and economic growth in Nigeria are investigated using an autoregressive distributed lag bounds test and vector error correction Granger causality. The result shows that financial development and remittances contribute positively to economic growth. Furthermore, findings from the moderating role suggest that financial development and remittances serve as substitutes to affect growth in the short run; however, financial development and remittances perform a complementary role in influencing economic growth in the long run. In addition, the causality tests indicate a one-way relationship from economic growth to financial development as well as bidirectional causality between remittances and financial development in the short run, while financial development and remittances Granger cause economic growth in the long run. The outcome of this study suggests there are time lags in the relationship between remittances, financial development, and economic growth in Nigeria. The implications of the findings are discussed.